Capitalism and Citizenship : the Impossible Partnership. - Dean, Kathryn (Critical realism--interventions., 2012)
Can capitalism and citizenship co-exist? In recent years advocates of the Third Way have championed the idea of public-spirited capitalism as the antidote to the many problems confronting the modern world. This book develops a multi-disciplinary theory of citizenship, exploring the human abilities needed for its practice. It then argues that capitalism impedes the nurturing of these abilities. In advancing these arguments, Kathryn Dean draws on the work of a wide range of thinkers including Freud, Marx, Lacan, Habermas and Castells.